Методичний підхід до аналізу основних параметрів страхового ринку - Болотських, Т.В. (Економіка промисловості, 2012)
Запропоновано методику аналізу попиту на страховому ринку на основі функції очікуваної корисності Неймана-Моргенштерна. Розроблено підхід до розрахунку ринкової частки страхової компанії, реальної та потенційної ємкості страхового ринку, що дозволяє оцінити ринкове становище компанії.
Ключові слова: страховий ринок, попит, частка ринку, місткість ринку. Предложена методика анализа спроса на страховом рынке на основе функции ожидаемой полезности Неймана-Моргенштерна. Разработан подход к расчету рыночной доли страховой компании, реальной и потенциальной емкости страхового рынка, позволяющий оценить рыночное положение компании.
Ключевые слова: страховой рынок, спрос, доля рынка, емкость рынка. Insurance market of Ukraine is characterized by growth of competition between domestic insurance companies and increased activity of foreign insurance companies. This calls for more research in the theory of market development, adaptation of the existing methodological approaches to the insurance market peculiarities.
An approach to analysis of demand for insurance market based on the theory of expected utility is proposed in the article. The proposed approach to the analysis of the demand for insurance services enables the prediction of specific behavior of insurers under various changes in the insurance market parameters. The proposed approach to the analysis of the demand for insurance services allows predicting specific behavior of insurers under various changes in the insurance market parameters. Methodical approaches to calculation and analysis of individual indicators of market development are proposed in the article. The capacity (potential capacity) of the insurance market is the potential volume of premiums insurers that may be charged within a particular insurance market segment. In order to calculate the market share of insurance company it is proposed to use an approach based on the retail audit. The method can also be defined: changing current insurance market share through changing the amount of insurance premiums, insurance premiums predict a change in market share of a company and the constant development of the market segment, calculate the potential market share at different levels of development of a particular market segment and constant volume of insurance premiums, calculate the potential amount of premiums at different levels of development of a particular market segment and constant real market share of the company. Analysis of the basic market parameters for the proposed method allows the management of insurance company to model different states of the chosen market segment.
Keywords: insurance market, demand, market share, market capacity.